INTERPRETATION AND JUSTIFICATION OF RULES FOR MANAGERS IN BUSINESS ORGANIZATIONS: A PROFESSIONAL ETHICS PERSPECTIVE: Received: 18th July 2023; Revised: 27th October 2023, 29th November 2023, 24th December 2023; Accepted: 01st January 2024 - Sachdev, Kumar Neeraj (PEOPLE: International Journal of Social Sciences, 2024)
Managers’ roles and corresponding obligations in business organizations are well-established. If a conflict in competing obligations arises, then the concerned manager is generally advised to consult and apply rules as they exist in the form of various laws, policies and guidelines in the country, the profession or the industry, and the organization. These three sets of rules are formulated to help explain an organization’s work to managers and others so that they may understand and arrive at judgments to act in the given fact-situations appropriately. However, the rule-following of managers, it is argued, ought to be ethically correct for its own sake and for the sake of the ethical environment in the organization. For this purpose, the managers ought to interpret the rules for their correct applications, in fact-situations, instead of just following the rules. They ought to look for a rational interpretation of rules so they do not compromise their managerial responsibilities, as it is a question of understanding not only letters of rules but also the spirit of rules. The argument continues that apart from understanding the reasons for the rational interpretation of rules, there is also a need to assess the ethical justification of rules because, for example, a professional manager may come across a rule regarding gender discrimination or else he may not find any rule regarding unjust dismissal from the job in his organization. Given the above, I argue in the paper that the rule-following of managers in the organization is ethically required to be rooted in their ability to interpret and ethically justify rules rationally.